Treat to target versus standard of care for patients with Crohn's disease treated with ustekinumab (STARDUST): an open-label, multicentre, randomised phase 3b trial. (April 2022) - Danese, Silvio; Vermeire, Severine; D'Haens, Geert; Panés, Julian; Dignass, Axel; Magro, Fernando; Nazar, Maciej; Le Bars, Manuela; Lahaye, Marjolein; Ni, Lioudmila; Bravata, Ivana; Lavie, Frederic; et al.
Summary: Background: A treat-to-target strategy, in which strictly defined treatment targets facilitate decision making in clinical practice, is advocated as an optimised management approach for some chronic disorders. The aim of the STARDUST trial was to assess whether a treat-to-target strategy with early endoscopy, regular biomarker and clinical symptom monitoring, and dose intensification for persistent inflammatory activity, was more successful in achieving endoscopic improvement at week 48 than a clinically driven maintenance strategy in patients with moderate-to-severe active Crohn's disease receiving ustekinumab. Methods: This open-label, multicentre, randomised phase 3b trial included adults with active, moderate-to-severe Crohn's disease (Crohn's Disease Activity Index [CDAI] 220–450 and Simple Endoscopic Score in Crohn's Disease [SES-CD] ≥3) for whom conventional therapy or one biologic therapy, or both, had failed. Patients received intravenous ustekinumab approximating 6 mg/kg at baseline and subcutaneous ustekinumab 90 mg at week 8. At week 16, patients with a CDAI improvement of 70 or more points from baseline were randomly assigned (1:1) to receive standard-of-care or treat-to-target maintenance treatment through week 48. Randomisation was balanced by using randomly permuted blocks and was stratified by biologic history status and baseline SES-CD score. All patients who signed informed consent, who were not screening failures, and who received at least one dose of study treatment were included in week 16 analyses. All patients included in week 16 analyses and randomly assigned to one of the maintenance treatment regimens were included in the week 48 efficacy and safety analyses (ie, on an intention-to-treat basis). Patients assigned to the treat-to-target arm received ustekinumab every 12 weeks or every 8 weeks based on SES-CD improvement from baseline and could escalate to every 4 weeks through week 48 if prespecified targets were missed. Patients assigned to the standard-of-care arm received ustekinumab every 12 weeks or every 8 weeks; those receiving treatment every 12 weeks could escalate per European labelling. The primary efficacy endpoint was endoscopic response at week 48 (SES-CD score ≥50% decrease from baseline), analysed by non-responder imputation. This trial is registered at ClinicalTrials.gov, NCT03107793, and is active but not recruiting. Findings: 498 patients received standard induction treatment, of whom 440 were randomly assigned to the treat-to-target group (n=219) or the standard-of-care group (n=221). At week 48, there was no significant difference in endoscopic response (83 [38%] of 219 patients vs 66 [30%] of 221 patients; p=0·087), endoscopic remission (25 [11%] vs 32 [15%]; p=0·334), mucosal healing (31 [14%] vs 37 [17%]; p=0·449), and clinical remission (135 [62%] vs 154 [70%]; p=0·072) between the two groups; clinical response was significantly lower in the treat-to-target group than in the standard-of-care group (149 [68%] vs 172 [78%]; p=0·020). Other endoscopic, clinical, and biomarker outcomes were generally not significantly different between groups. The most commonly reported treatment-emergent adverse events were nasopharyngitis (29 [13%] of 219 patients in the treat-to-target group vs 29 [13%] of 221 patients in the standard-of-care group), abdominal pain (23 [11%] vs 19 [9%]), arthralgia (24 [11%] vs 19 [9%]), and headache (24 [11%] vs 21 [10%]). Interpretation: Timely escalation of ustekinumab therapy for patients with Crohn's disease, based on early endoscopic response, clinical symptoms, and biomarkers, did not result in significantly better endoscopic outcomes at week 48 than symptom-driven decisions alone. Future studies need to confirm if some subgroups of patient might benefit from a treat-to-target strategy with ustekinumab. Funding: Janssen-Cilag.